2011
DOI: 10.1159/000324594
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Efficacy and Safety in Children with Vesicoureteral Reflux of a Single Injection of Two Different Bulking Agents – Polydimethylsiloxane (Macroplastique) or Dextranomer/Hyaluronic Acid Copolymer (Deflux): A Short-Term Prospective Comparative Study

Abstract: Purpose: To compare the clinical efficacy and safety in children with vesicoureteral reflux (VUR) of a single injection of two different bulking agents: polydimethylsiloxane (Macroplastique) or dextranomer/hyaluronic acid copolymer (Deflux). Methods: A total of 73 patients (106 renal units, 41 boys and 32 girls) aged 2–15 years (mean age, 34.5 months) were included. A single subureteral injection of either Macroplastique or Deflux was performed in 37 children (55 ureters) and 36 children (51 ureters), respecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 51 publications
0
5
0
1
Order By: Relevance
“…Today, Dx/HA is the most widely used substance -and the only approved by the Food and Drug Administration (FDA). However, although polydimethylsiloxane has not been approved in children yet, efficacy in the pediatric population has been widely acknowledged in the literature (15)(16)(17) . In our study, similarly to what Williams G et al reported in their 2019 meta-analysis (18) , healing rates were similar with both materials.…”
Section: Discussionmentioning
confidence: 99%
“…Today, Dx/HA is the most widely used substance -and the only approved by the Food and Drug Administration (FDA). However, although polydimethylsiloxane has not been approved in children yet, efficacy in the pediatric population has been widely acknowledged in the literature (15)(16)(17) . In our study, similarly to what Williams G et al reported in their 2019 meta-analysis (18) , healing rates were similar with both materials.…”
Section: Discussionmentioning
confidence: 99%
“…Our results are consistent with those reported by the authors who did not see a significant difference in cure rates when comparing Dx/HA and Macroplastique. [28][29][30] Even if no statistical difference was shown between both products, the price difference is an important consideration in choosing a bulking agent.…”
Section: Discussionmentioning
confidence: 99%
“…Hoy en día la sustancia más utilizada, y la única aprobada por la Food and Drug Administration (FDA), es el Dx/HA. No obstante, a pesar de que el uso de polidimetilsiloxano no esté aprobado en niños, su eficacia en esta población está ampliamente recogida en la literatura (15)(16)(17) . En nuestro estudio, al igual que lo publicado por Williams y cols.…”
Section: Discussionunclassified